Bioactif and Bioactivity Test of Moringa (Moringa sp.), Starfruit Wuluh (Averrhoa bilimbi), and Keres (Muntingia calabura) - Indah Ttriwahyuni Latifah; Rofiatun Solekha; Nur Fatimah Azzahra Haibaturrahma; Ayu Dewi Wulandari; Rieke Dwi Ayuni; Salasun Nisa; Syafiq Alfanani; Muhammad Syahrur Ramadhan; Arsanul Khakim (BEST Journal (Biology Education, Sains and Technology), 2025)
This study evaluated the bioactivity of Moringa plant extracts (Moringa oleifera), Star Fruit Wuluh (Averrhoa bilimbi), and Keres (Muntingia calabura) on antioxidant and antibacterial activities. Extraction was carried out using the maceration method with a 96% ethanol solvent. The antioxidant test was carried out using the DPPH method (2,2-diphenyl-1- picrylhydrazyl), while the antibacterial test was carried out on Staphylococcus aureus bacteria using the well diffusion method. The results showed that Moringa extract had a strong linear relationship between concentration and antioxidant activity, while Star Fruit and Keres extracts showed low antioxidant activity with IC50 values above 100 ppm, indicating weak activity. In the antibacterial test, Star Fruit extract produced a significant inhibition zone, although it was classified as a weak response. These findings suggest that all three plants have potential as sources of bioactive compounds, although optimal efficacy requires optimization of extraction and concentration methods. Further research is needed to identify the main active compounds and explore their mechanisms of action.